Analyses of an expressed sequence tag library from Taenia solium, Cysticerca. - Jonas Lundström; Fernando Salazar-Anton; Ellen Sherwood; Björn Andersson; Johan Lindh (Public Library of Science (PLoS), 2010)
BACKGROUND: Neurocysticercosis is a disease caused by the oral ingestion of eggs from the human parasitic worm Taenia solium. Although drugs are available they are controversial because of the side effects and poor efficiency. An expressed sequence tag (EST) library is a method used to describe the gene expression profile and sequence of mRNA from a specific organism and stage. Such information can be used in order to find new targets for the development of drugs and to get a better understanding of the parasite biology. METHODS AND FINDINGS: Here an EST library consisting of 5760 sequences from the pig cysticerca stage has been constructed. In the library 1650 unique sequences were found and of these, 845 sequences (52%) were novel to T. solium and not identified within other EST libraries. Furthermore, 918 sequences (55%) were of unknown function. Amongst the 25 most frequently expressed sequences 6 had no relevant similarity to other sequences found in the Genbank NR DNA database. A prediction of putative signal peptides was also performed and 4 among the 25 were found to be predicted with a signal peptide. Proposed vaccine and diagnostic targets T24, Tsol18/HP6 and Tso31d could also be identified among the 25 most frequently expressed. CONCLUSIONS: An EST library has been produced from pig cysticerca and analyzed. More than half of the different ESTs sequenced contained a sequence with no suggested function and 845 novel EST sequences have been identified. The library increases the knowledge about what genes are expressed and to what level. It can also be used to study different areas of research such as drug and diagnostic development together with parasite fitness via e.g. immune modulation.